Peranan Guru Pendidikan Agama Kristen Dalam Membangun Karakter Kriastiani Siswa - Remala Lase (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was conducted at SD Negeri 075022 Mazingo Tabaloho. This study used a qualitative descriptive method. This study aims to determine whether Christian religious education teachers play their role in building the Christian character of students at SD Negeri 075022 Mazingo Tabaloho. Based on research carried out, the role of Christian religious education teachers has increased in building the Christian character of students at SD Negeri 075022 Mazingo Tabaloho in the 2018/2019 academic year, so that the Christian character of students is correct by testing the hypothesis with a significant (a) 0.05 or 0.95% variable X is known to be 0.436. This, there is a role for Christian religious education teachers in building the Christian character of students at SD Negeri 075022 Mazingo Tabaloho for the 2018/2019 academic year. However, the Christian religious education teacher at SD Negeri 075022 Mazingo Tabaloho 2018/2019 academic year has not fully carried out its role and the main problem is not fully fulfilled the role of Christian religious education teachers, namely students do not follow school rules. Keywords: learning outcomes; Christian character  Abstrak: Penelitian ini dilaksanakan di SD Negeri 075022 Mazingo Tabaloho,  Penelitian ini peneliti menggunakan metode deskriptif kualitatif. Penelitian ini bertujuan untuk Untuk mengetahui apakah guru pendidikan agama Kristen menjalankan perannya dalam membangun karakter Kristiani siswa di SD Negeri 075022 Mazingo Tabaloho. Berdasarkan penelitian yang dilaksanakan peranan guru pendidikan agama Kristen meningkat dalam membangun karakter Kristiani siswa di SD Negeri 075022 Mazingo Tabaloho Tahun Pelajaran 2018/2019, sehingga karakter Kristiani siswa menjadi benar dengan  Uji hipotesis dengan signifikan (a) 0,05 atau 0,95% variabel X diketahui sebesar 0,436. Hal ini, terdapat peranan guru pendidikan agama Kristen dalam membangun karakter Kristiani siswa di SD Negeri 075022 Mazingo Tabaloho Tahun Pelajaran 2018/2019. Namun  Guru pendidikan agama Kristen di SD Negeri 075022 Mazingo Tabaloho Tahun Pelajaran 2018/2019 belum sepenuhnya melaksanakan peranannya dan Masalah utama tidak sepenuhnya terlaksana peranan guru pendidikan agama Kristen, yakni siswa kurang mengikuti aturan sekolah. Kata kunci: hasil belajar; karakter Kristiani